The Enactment of Fast and Slow Time Regimes by Urban Retail and Consumer Services - Cachinho, Herculano (2021)
This article discusses the enactment of conflicting time regimes in contemporary urban retail and consumer services. We draw on the theories of time–space compression, social acceleration, and the fast–slow dichotomy to argue that retail and consumer services act on urban life by enacting two apparently conflicting time regimes: fast time and slow time. Although retail and consumer services are not able to establish urban time regimes by themselves, they enact time regimes in their stores by offering the temporal resources that consumers need to perform their preferred timestyles. These temporal resources stem from the store’s concepts, sales model and management strategies, and ambiances. We draw on our ongoing field research in Colinas do Cruzeiro, an upper middle-class suburban neighborhood in greater Lisbon, Portugal, which has included field surveys, nonparticipant observation, and semistructured interviews. Our findings identify three time regimes that retail and consumer services in Colinas do Cruzeiro enact in their stores. This finding allows us to understand the processes through which retail, consumer services, and urban rhythms tend to synchronize. We discuss the geographical implications of understanding the processes that underpin the enactment of time regimes in contemporary urban retail and consumer services.